Sociodemographic and clinical profile of 49 patients with oral lichen planus: a 10-year retrospective study (Research, Society and Development, 2022)
Considering a few epidemiologic studies which describes clinic and pathologic features and prevalence of oral lichen planus (OLP) in Brazil as well as the importance of such studies in order of health care services plans and to verify changes along the years, the present study aimed to evaluate the sociodemographic and clinical profile of 49 participants diagnosed with OLP during a period of ten years. For the sample selection, the clinical and histopathological criteria for the diagnosis of OLP proposed by the American Academy of Oral and Maxillofacial Pathology were used, except for the criterion “absence of epithelial dysplasia”. Most individuals were female (75.5%; p = 0.0005). White individuals were significantly older than the black individuals (67.7 vs 49.2 years; p = 0.001). Lesions affecting multiple bilateral/symmetric sites were more common than lesions in a single bilateral/symmetric site (77.6%; p = 0.0001). The most commonly affected sites were buccal mucosa (85.7%), tongue (65.3%), gingiva (42.9%), and lips (32.7%). Most lesions were white (reticular pattern was found in 93.9% and plaque in 75.5% of cases). Plaque pattern was more common in older individuals (p = 0.006). During the different moments of evaluations some individuals did not meet the American Academy of Oral and Maxillofacial Pathology criteria due to the absence of oral lesions with multifocal symmetric distribution. Therefore, in a first consultation, if the patient does not present multifocal symmetric distributed lesions, the diagnosis of OLP cannot be excluded and the patient should be followed-up.